2018
DOI: 10.3390/jof4010009
|View full text |Cite
|
Sign up to set email alerts
|

Patient Susceptibility to Candidiasis—A Potential for Adjunctive Immunotherapy

Abstract: Candida spp. are colonizing fungi of human skin and mucosae of the gastrointestinal and genitourinary tract, present in 30-50% of healthy individuals in a population at any given moment. The host defense mechanisms prevent this commensal fungus from invading and causing disease. Loss of skin or mucosal barrier function, microbiome imbalances, or defects of immune defense mechanisms can lead to an increased susceptibility to severe mucocutaneous or invasive candidiasis. A comprehensive understanding of the immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 139 publications
(204 reference statements)
0
21
0
1
Order By: Relevance
“…In addition to the inhibition by gut microbiota, neutrophil can also provide protection against Candida invasion by killing engulfed fungi through oxidative and non-oxidative mechanisms, or by trapping extracellular fungi by neutrophil extracellular traps (NETs) ( Netea et al, 2015 ; Davidson et al, 2018 ). If the hyphal form grows excessively, epithelial cells can produce inflammatory mediators to recruit innate immune cells to clear fungal infections ( Naglik et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the inhibition by gut microbiota, neutrophil can also provide protection against Candida invasion by killing engulfed fungi through oxidative and non-oxidative mechanisms, or by trapping extracellular fungi by neutrophil extracellular traps (NETs) ( Netea et al, 2015 ; Davidson et al, 2018 ). If the hyphal form grows excessively, epithelial cells can produce inflammatory mediators to recruit innate immune cells to clear fungal infections ( Naglik et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…These pathogens and their byproducts can trigger inflammasome activation. Candida spp., frequently found in peri-implantitis lesions, can induce activation of the NLRP3 inflammasome (282). LPS from P. gingivalis, another peri-implantitis-related pathogen, increases the mRNA levels of NLRP3, ASC, and caspase-1 in BMSCs, thereby increasing IL-1b production (147).…”
Section: Inflammasomes In Peri-implantitismentioning
confidence: 99%
“…Nevertheless, clinical evidence has shown that dental prosthetic devices, mainly based on PMMA resins, undergo a proliferation of C. albicans infections [3,4,5], which affects their lifetime. Indeed, C. albicans is a pleomorphic fungus that is commensal of gastrointestinal microbiota [5] and, in case of immunodeficiency, the frequency of candidiasis can increase [6,7,8].…”
Section: Introductionmentioning
confidence: 99%